On the approximation and stability of linear systems with delay - Piddubna, Larissa (Moldova State University, 2022)
This paper investigates the application of approximation schemes for differential-difference equations [1-3] to construct algorithms for the approximate finding of nonsymptotic roots of quasipolynomials and their application to study the stability of solutions of systems of linear differential equations with delay.
Keywords: stability,approximation, linear systems with delay